Researching the Literary Creativity of Slovenian Female Writers at the Turn of the 20th and 21st Centuries - Borovnik, Silvija (Slavistična prepletanja 6, 2025)
The article focuses on the research into works by Slovenian women writers in the history of Slovenian literature, based on the following selected publications: Do Women Write Differently? (1995), Narrative Prose in Slovenian Literature III (ed. Jože Pogačnik, 2011), Call Me by Name (2013), Literary Studies (2012), Multiculturalism and Interculturality in Slovenian Literature (2017) and Seeing Oneself in the Other: Slovenian Literature in an Intercultural Context (2022). It analyses mainly the prose works of Slovenian women authors from the second half of the 19th century to the present, which are also included in the canon of Slovenian literary history.